DYNAMIC CAPABILITIES UMKM TEH TUBRUK DALAM MENGHADAPI TREN MINUMAN KEKINIAN UNTUK MENINGKATKAN DAYA SAING DI LINGKUNGAN KAMPUS UIN RADEN INTAN LAMPUNG - Hayati, Ella; Prameswari, Nadira Isaura; Sanjaya, Vicky F (TANSIQ: Jurnal Manajemen dan Bisnis Syariah, 2025)
This research seeks to investigate how dynamic capabilities are utilized by Teh Tubruk MSMEs to address the rising trend of contemporary beverages among students at UIN Raden Intan Lampung. This is aimed at boosting their business competitiveness. The theme was selected because the surge in modern beverage popularity challenges the longevity of traditional products. We adopted a descriptive qualitative method, focusing on the campus vicinity, with MSME owners, students, and cooperative managers as the primary informants. We gathered data via in-depth interviews, field observations, and documentation, then applied the Miles and Huberman model for analysis. The findings reveal that MSME operators demonstrate sensing abilities to detect changes in consumer tastes, capacity to seize opportunities through innovative products and inventive marketing, and transformation capabilities to adapt resources and business models accordingly. The study confirms that dynamic capabilities are vital in enhancing the competitiveness of traditional MSMEs amidst modernized markets and promoting business sustainability through adaptive innovation